Model Enterprise Resouce Planning Sistem Informasi Akademik Menggunakan Togaf Pada Universitas Peradaban - Mukrodin Mukrodin; Oman Somantri (Politeknik Harapan Bersama, 2019)
The progress of information systems in the education sector is so developed that it requires to carry out academic activities online. To implement and facilitate the acceleration of higher education, the University of Peradaban as the organizer of higher education in the Bumiayu Subdistrict of Brebes Regency, currently does not have an information system that is integrated with academic information systems (SIA), therefore an information system needs analysis. The Togaf Framework is a framework that can see problems and the development of a comprehensive information system. The goal is to build a model Eneterprise Resource Planing academic information system to support the strategy of developing academic information systems as needed at the University of Peradaban. The type of research used is qualitative research that is explorative, which is to look deeply into the needs of users in applying academic information systems at the University of Peradaban. Analysis of the planner's scope, SIA is designed to manage Lecturer data, Student data, class schedules, Card Management Study Plan, Study Card processing and management of value transcripts and alumni data management. System development consists of three parts, namely a system that can be used by academic administrative staff, lecturers and can be used by students. SIA is designed to provide speed and convenience in managing data and academic development for the competitiveness of universities.